A tale of two plains: migrating landscapes between Italy and Argentina 1870–1955. Issue 2 (May 2021) - Valisena, Daniele; Canovi, Antonio
Abstract : This article offers an analysis of the encounter between the two natural environments of the Italian Po Plain and the Argentinian Pampa Gringa through the migration of Italian rural workers. Notably, we focus on the migration micro-histories of Emiliano-Romagnoli, who moved from Italy to Argentina during Italian Great Migration Era (1870–1955). Building on oral histories gathered in Italy and Argentina between 2005 and 2007, these micro-histories show how place-based landscapes of Italianness hybridised with the local landscape of the South American plains through Italian migrants' embodied memories, labour, and socio-environmental transformation practices. By focusing on Po Plain migrants' memories and experiences of the lowlands of northern Italy and the Argentinian pampas, we aim to offer a micro-historical perspective on the environmental history of migration.